The impact of new national guidance for the public health management of enteric fever in England. (January 2018) - Russell, K.; Addiman, S.; Grynszpan, D.; Freedman, J.; Lopez Bernal, J.; Yin, Z.; Rawlings, C.; Balasegaram, S.
Abstract: Objectives: New guidance was published in England in February 2012 to support the public health management of enteric fever and reduce the risks of secondary transmission. The new guidance was evaluated to assess: The impact of reduced sampling schedules on secondary transmission of enteric fever. The burden, compliance and yield associated with sampling. User acceptability. Study design: Quantitative and qualitative evaluation of the implementation of new public health guidance. Methods: A qualitative review of all non-travel–related cases from February 2010 to January 2014 to compare the risk of secondary transmission before and after the guidance introduction; an audit of clearance sampling for each case and their contacts reported in London from February 2012–January 2015 to compare with a previous London audit; and an online user survey in November 2014. Results: The proportions of non-travel cases reported before and after the introduction of the new guidance were similar, 6% in 2010–2012 compared to 7% in 2012–2014 ( P = 0.33). There was a 32% reduction in the number of clearance samples required for cases and the estimated period of exclusion from work or school was reduced from 54 days to 16 days. Compliance in case clearance improved from 53% to 90% and contact screening compliance improved from 42% to 80%. The targeted screening of contacts led to a significantly higher positive yield (3.6% from 1.5%, P = 0.003). All symptomatic co-travellers presented to a healthcare professional, suggesting that screening could be restricted to those in risk groups for transmission. Feedback from users highlighted additional areas, such as management of large organised groups of co-travellers and those diagnosed abroad, which has informed the update of the national guidance. Conclusions: The new guidance has not led to an increase in secondary transmission of enteric fever in England and findings have been used to inform an update of the guidance. The new guidance also represents a reduced burden of investigation and thus a likely reduced cost to patients, healthcare professionals, laboratories and environmental health officers. Highlights: New guidance on public health management of enteric fever was published in 2012. The proportion of non-travel cases before and after the new guidance was similar. The number of clearance samples and the exclusion period required have reduced. Compliance with clearance or screening samples improved. The guidance has not led to an increase in secondary transmission of enteric fever.